Cr() adsorption from aqueous solution by an agricultural waste based carbon - Khan, Taimur; Isa, Mohamed Hasnain; Ul Mustafa, Muhammad Raza; Yeek-Chia, Ho; Baloo, Lavania; Binti Abd Manan, Teh Sabariah; Saeed, Mohamed Osman (RSC advances, 2016)
The study examined the adsorption of hexavalent chromium [Cr( vi )] from aqueous solution by acidically prepared rice husk carbon (APRHC). APRHC was characterized in terms of surface area, micropore area, micropore volume, average pore diameter and surface morphology. The effects of pH, contact time, initial Cr( vi ) concentration and adsorbent dose on the adsorption of Cr( vi ) from aqueous solution were investigated. Batch adsorption tests showed that Cr( vi ) adsorption depends on initial concentration, contact time and pH. Equilibrium adsorption was achieved in 120 min, while maximum Cr( vi ) adsorption occurred at pH 2. An artificial neural network (ANN) was used to model Cr( vi ) adsorption. The Levenberg-Marquardt (LM) training algorithm was found to be the best among the 11 backpropagation (BP) algorithms tested, with a lowest mean square error (MSE) of 8.8876 and highest coefficient of determination ( R 2 ) of 0.987. Adsorption of Cr( vi ) by APRHC followed pseudo-second order kinetics. Langmuir and Freundlich isotherm equations were fitted to the equilibrium adsorption data; the former isotherm yielded a better fit. The thermodynamic results indicate that the process of Cr( vi ) adsorption by APRHC was endothermic in nature. Desorption of Cr( vi ) was very low, i.e. in the range from 0.1 to 9%. Cr( vi ) adsorption capacity by APRHC was compared with that of various adsorbents. APRHC showed a high capacity for adsorption of Cr( vi ). APRHC can be employed as an effective adsorbent and substitute for commercially available activated carbon for the removal of Cr( vi ) from aqueous solutions and wastewater systems. The study examined the adsorption of hexavalent chromium [Cr( vi )] from aqueous solution by acidically prepared rice husk carbon (APRHC).